1999
DOI: 10.1086/314729
|View full text |Cite
|
Sign up to set email alerts
|

Association of Major Histocompatibility Complex Determinants with the Development of Symptomatic and Asymptomatic Genital Herpes Simplex Virus Type 2 Infections

Abstract: The clinical spectrum of herpes simplex virus (HSV) infections, ranging from asymptomatic to frequently distressing outbreaks, suggests that there may be immunologic determinants of disease severity that are associated with human leukocyte antigen (HLA) expression. A controlled, prospective study identified several major histocompatibility complex (MHC) class I and II antigens whose frequencies are associated with HSV-2 infection or with frequent symptomatic genital recurrences. Previous studies were hampered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 55 publications
0
50
2
Order By: Relevance
“…Based on the fact that HSV-1 enters, replicates, spreads, and establishes latent infections with virtually identical efficiencies in C57BL/6 and BALB/c mice, individuals of the species Mus musculus do not appear to differ fundamentally in their innate resistance to HSV-1 infection. Likewise, although it has been implied that differences in host resistance are relevant in explaining what differentiates humans with recurrent herpetic disease from the vast majority of asymptomatic carriers of HSV-1 and HSV-2 (15,29,31,33), there is little epidemiological evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that HSV-1 enters, replicates, spreads, and establishes latent infections with virtually identical efficiencies in C57BL/6 and BALB/c mice, individuals of the species Mus musculus do not appear to differ fundamentally in their innate resistance to HSV-1 infection. Likewise, although it has been implied that differences in host resistance are relevant in explaining what differentiates humans with recurrent herpetic disease from the vast majority of asymptomatic carriers of HSV-1 and HSV-2 (15,29,31,33), there is little epidemiological evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One genetic mechanism may be immunologic determinants of disease severity that are associated with HLA expression. A prospective study of 146 subjects has identified several HLA alleles that are associated with HSV-2 infection or with frequent symptomatic genital recurrences (40). Most significantly, the presence of HLA-B8 and the absence of HLA-B27 and -Cw2 were associated with symptomatic disease in HSV-2-infected subjects, and HLA-Cw4 was significantly associated with HSV-2 infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…Early in the development of recurrent lesions, HSV-1-specific IFN-␥-producing CD4 ϩ T cells that display a cytotoxic activity predominate in the mononuclear infiltrate surrounding HSV-1-infected epidermal cells, which strongly express HLA-DR (47). For many years, the association of HLA-DR haplotypes with susceptibility to both labial and genital herpes has been appreciated (27,41,44,55). Among the HLA-DR alleles, DRB1*04, DRB1*07, DRB1*11, and DRB1*13 are most frequent in the populations studied (26,35,41,55).…”
mentioning
confidence: 99%
“…For many years, the association of HLA-DR haplotypes with susceptibility to both labial and genital herpes has been appreciated (27,41,44,55). Among the HLA-DR alleles, DRB1*04, DRB1*07, DRB1*11, and DRB1*13 are most frequent in the populations studied (26,35,41,55). DRB1*13 is frequently seen in symptomatic HSV infection, while DRB1*04 is most frequent in individuals with asymptomatic HSV infection (41).…”
mentioning
confidence: 99%